Application of fuzzy logic in a secure beacon-based guidance system for public transportation - Molina-Gil, Jezabel; Caballero-Gil, Pino; Quesada-Arencibia, Alexis; Blasio, Gabriele Salvatore de (Zielona Góra: Uniwersytet Zielonogórski)
Promoting the use of public transport is increasingly urgent in our society, both to reduce traffic congestion, air pollution and stress levels, and to ensure the high level of mobility demanded by citizens. The lack of continuous on-trip assistance for public transport users discourages many travellers. Thus, the main objective of this work is to design a personal digital travel companion for outdoor location and event detection based on Bluetooth Low Energy, which can be used for intelligent transport technology. After analysing the functional requirements, the proposal is implemented as a mobile application for beacon-based event detection.
Keywords: public transport; guidance; location system; Bluetooth Low Energy; fuzzy logic